Evolutionary differences in gene loss and pseudogenization among mycoheterotrophic orchids in the tribe Vanilleae (subfamily Vanilloideae) - Zhou, Lisi; Chen, Tongyao; Qiu, Xiandan; Liu, Jinxin; Guo, Shunxing (Frontiers in Plant Science, 2023)
Galeola lindleyana is a mycoheterotrophic orchid belonging to the tribe Vanilleae within the subfamily Vanilloideae. In this study, the G. lindleyana plastome was assembled and annotated, and compared with other Vanilleae orchids, revealing the evolutionary variations between the photoautotrophic and mycoheterotrophic plastomes. The G. lindleyana plastome was found to include 32 protein-coding genes, 16 tRNA genes and four ribosomal RNA genes, including 11 pseudogenes. Almost all of the genes encoding photosynthesis have been lost physically or functionally, with the exception of six genes encoding ATP synthase and psaJ in photosystem I. The length of the G. lindleyana plastome has decreased to 100,749 bp, while still retaining its typical quadripartite structure. Compared with the photoautotrophic Vanilloideae plastomes, the inverted repeat (IR) regions and the large single copy (LSC) region of the mycoheterotrophic orchid’s plastome have contracted, while the small single copy (SSC) region has expanded significantly. Moreover, the difference in length between the two ndhB genes was found to be 682 bp, with one of them spanning the IRb/SSC boundary. The Vanilloideae plastomes were varied in their structural organization, gene arrangement, and gene content. Even the Cyrtosia septentrionalis plastome which was found to be closest in length to the G. lindleyana plastome, differed in terms of its gene arrangement and gene content. In the LSC region, the psbA, psbK, atpA and psaB retained in the G. lindleyana plastome were missing in the C. septentrionalis plastome, while, the matK, rps16, and atpF were incomplete in the C. septentrionalis plastome, yet still complete in that of the G. lindleyana. Lastly, compared with the G. lindleyana plastome, a 15 kb region located in the SSC area between ndhB-rrn16S was found to be inverted in the C. septentrionalis plastome. These changes in gene content, gene arrangment and gene structure shed light on the polyphyletic evolution of photoautotrophic orchid plastomes to mycoheterotrophic orchid plastomes. Thus, this study’s decoding of the mycoheterotrophic G. lindleyana plastome provides valuable resource data for future research and conservation of endangered orchids.